General amnesty and its impact on the pleadings of criminal and disciplinary proceedings General Amnesty Law in the Kurdistan Region of Iraq No. 4/2017 as a model Comparative analytical study - واوۆسجاى یاریدەدەر ئووێد سٍعید خضر; واوۆسجاى یاریدەدەر حٍسٍن وسجٍفا حوسێي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
General amnesty is a legal proceeding and the legislative authority regulates its provisions by enacting a law and publishing it in the gazette. The provisions of this law are enforced by the executive and judicial authority. The aim of enacting general amnesty law in most countries is to mitigate the burden of the State economically in terms of bearing the vast number of sentenced and detained persons, in addition to the revision of criminal policy, fields of criminal reform and bringing the convicted persons into the society. After changing the political system of Iraq and remaining Kurdistan within the scope of Iraqi federal, three general amnesty laws have been enacted which are: General Amnesty law in KurdistanIraq No. 4 of 2007, General Amnesty law in Kurdistan-Iraq No. 2 of 2012 and the last law is the general Amnesty law in Kurdistan No. 4 of 2017. This research is an attempt to analyze the general provisions of general amnesty and to analyze the provisions of the General amnesty law in Iraq and Kurdistan. It also provides the judicial case of courts of Kurdistan on general amnesty.